A Land Use Plan for A Border Town : Case Study of Chiang Khong Border Town, Wiang Sub-district Municipality, Chiang Khong District, Chiang Rai Province - Auttarat, Sudarat; Srivanit, Manat (Journal of Architectural/Planning Research and Studies (JARS), 2019)
The main objective of this research was to study land use situation in Wiang Sub-district Municipality, Chiang Khong District, Chiang Rai Province. It also aimed to study land use problems and land use requirements from. This is to propose land use guidelines to solve Chiang Khong border town’s land use problems. Research methods comprised of surveying, interviewing and focused-group brainstorming. The study indicated that, land use in the area of Wiang sub-district Municipality faced external and internal changes, for instance: forest area reduction, the extended urban development at the southern area of Wiang sub-district municipality, illegal land ownership, encroachment of forest areas for agriculture, and under-utilized land. So, future land use plan should focus on land use control for both natural or environmental preservation and community growth.